Fisiografia da região média da bacia hidrográfica do rio Itapemirim, ES - Lima, Jenesca Florencio Vicente de (2021)
The south of Espírito Santo has peculiar morphological, hydrographic and geological characteristics, which resulted in a great diversity of soils. Therefore, it is necessary to hierarchize geographical areas, separating them into geomorphological units. Geomorphological units are areas that have similar pedological, geological and geomorphological attributes. Therefore, this work had as main objective to characterize the geomorphological units referring to the soils of the middle region of the Itapemirim river hydrographic basin through physical, chemical and magnetic analysis. This characterization took place in three chapters. In Chapter 1, more detailed geomorphological units were delimited through multivariate analysis of morphometric, hydrological and magnetic data. In Chapter 2, the detailed mapping of areas vulnerable to flood risk was carried out using the fuzzy logic methodology. In Chapter 3, the physical, chemical and magnetic characterization of the geomorphological units was performed. As a result, eight units were delimited, namely: alluvial plains and terraces, depressions of mouns and gentles hills, stepped level of structural plateau I, stepped level of structural plateau II, stepped level of intermediate plateau, stepped level of pontoons and mountain massifs, stepped level of hills and scarped mountains, stepped level of remnant plateau. The municipalities of Alegre, Jerônimo Monteiro, Muniz Freire, Castelo and Cachoeiro de Itapemirim have areas classified as very high vulnerability to flooding, in all situations presented, whether in case of annual or seasonal precipitation. Through factor analysis it was possible to analyze the environmental dynamics of physical, chemical and magnetic parameters in the area as a function of relief and parent material.